Changes in solar radiation and snow depths in March. Irkutsk - N.I. Ianchenko (Российская Арктика)
Snow cover is an integral and important component of the natural, climatic and economic characteristics of Siberia. In this regard, the article is devoted to the study of changes in the depth of snow cover in Irkutsk, obtained on the basis of exploratory scientific and organizational field studies at the site of the lower stadium of the Irkutsk National Research Technical University. Temperature measurements in layers along the height of snow cover were carried out using an autonomous automatic atmospheric-snow measuring complex and recalculated to the depth of snow cover. Solar radiation measurements were carried out using the Vantage sensor. The results of field measurements of temperature in the snow cover, solar radiation were interpreted and qualitative and quantitative characteristics of changes in the depth of snow cover and solar radiation in March were determined. The dynamics of snow cover depth in March 2021, 2023, 2024 are given. It was established that in March 2021 and 2024, a uniform melting of snow cover is observed, with negative correlation coefficients of -0.86 and -0.90, in March 2023, the correlation coefficient is -0.29. But intensive snow cover melting is observed in the third ten-day period of March in 2023, 2024. The dynamics of the daily sum of total solar radiation in March 2023 and 2024 is shown. A comparison of in-kind measurements in 2023 with actinometric data of the Irkutsk UGMS in 2023 was made. A comparison was made between the daily sum of total solar radiation and the depth of snow cover in March, and correlation coefficients were established.